Pemodelan dan Peramalan Harga Penutupan Saham Perbankan dengan Metode ARIMA dan Family ARCH - Devi Novanti; Hajrul Multazam; Novira Laily Husna; Ossy Sanityasa Rahajeng; Selfina L; Rani Nooraeni (Hasanuddin University, 2020)
Modelling the stock closing price stock is useful so that the investors are expected to be able to understand the situation of the stock, in order to make the right decision when they want to buy or sell their stocks. This study uses the ARIMA and Family ARCH methods in modelling the volatility of four banking stocks that are in high demand by the public, which are Bank BRI (BBRI), Bank BNI (BBNI), Bank Mandiri (BMRI), and Bank BCA (BBCA) from January 1st 2017 until January 31st 2020. Stock returns are modelled by using the ARIMA model, then proceeded with the heteroscedasticity testing. Based on the test, we obtained the results of BBRI, BMRI, and BBCA are heteroscedastic. While BBNI are homoscedastic. The volatility models obtained from the test are BBNI has ARIMA models ([6,13], 1, [6,13]), BBRI has ARI models ([2,24,28), 1,0) -ARCH (1), BMRI has an ARIMA (2,1,4) -GARCH (1,1) model, and BBCA has ARI ([1,2], 1,0) -GARCH (1,1) model. Based on the rising value of the stock price, we suggest the best stock for the investors is BBRI because it has the largest increase of 10% followed by BBCA and BMRI